ANALISIS SIFAT MEKANIK KOMPOSIT Al 2075 REINFORCEMENT DENGAN ELECTROLESS ABU DASAR BATUBARA - Adhi Setiawan; Arita Rochma Nilasari; M. Ari (2477 - 6165, 2016)
Aluminium composite 2075 manufacturing required a strenghthener such as bottom ash which has been through the electroless plating process that serves coating the bottom ash and sticks to aluminium casting process. The oxidation of 100oC produce 0,0126 µm Mg thickness oxidation, 200oC produce 0,0146 µm Mg thickness oxidation, and 300oC produces 0,0506 µm Mg thickness oxidation. Mechanical properties were tested by using worn-out test and hardness test based on new material function that will be used to replace existing disc brake material. Harness test showed that castings are using oxidized ash powder with higher temperature and produce resistant material than in low temperature. Casting mixture with oxidized bottom ash 100oC produce specific abrasion of 2,008 x 10-6mm2/kg, produce of1,814 x 10-6mm2/kg for oxidized 200oC, and produce of 1,675 x 10-6mm2/kg for oxidized 300oC. Keywords: Aluminium 2075, Bottom ash, Composite, Electroless plating, Hardness test, Worn-out test.